ANALISIS DESKRIPTIF CAPITAL EXPENDITURE DAN DAMPAKNYA TERHADAP PROFITABILITAS PT UNITED TRACTORS TBK TAHUN 2020–2024 - Nasution, Syarifuddin Hz; Novizar, Amelia (Politeknik Negeri Medan, 2025)
This study investigates the trends and interrelationship between Capital Expenditure (CapEx) and corporate profitability at PT United Tractors Tbk over the 2020–2024 period. Capital Expenditure represents long-term strategic investments in tangible fixed assets, while profitability is assessed through net income as a core indicator of financial performance. Employing a quantitative descriptive methodology, this research utilizes secondary data sourced from audited annual reports, official corporate publications, and regulatory disclosures. The empirical findings reveal considerable fluctuations in both CapEx and profitability during the observed period. The early years (2020–2021) were marked by investment conservatism due to macroeconomic uncertainty stemming from the COVID-19 pandemic, despite notable improvements in profitability. A substantial escalation in both CapEx and net income was observed in 2022, suggesting that capital investment began to yield positive operational outcomes. However, the subsequent years (2023–2024) exhibit a decoupling of this relationship, with rising or sustained CapEx levels accompanied by a decline in profitability, highlighting the lagged and potentially nonlinear nature of CapEx returns. These results underscore the critical importance of aligning investment strategies with operational efficiency and return realization timelines. The study concludes that while CapEx is essential to driving long-term growth and competitiveness, its contribution to profitability is contingent upon rigorous planning, execution, and post-investment evaluation. The insights derived may offer valuable implications for managerial decision-making, investor assessment, and future academic inquiry into capital allocation efficacy.